PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP NILAI PERUSAHAAN PERKEBUNAN SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2023 - Egi Delgia; Eri Bestary Al Haitamy; Pramesti Nurul Adinda (Journal of Applied Accounting And Business, 2025)
This research aims to determine the extent of the influence of tax planning and deferred tax expenses on company value. The population used in this research is palm oil plantation companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. The sample determination in this research was purpose sampling, with a sample of 9 companies. The type of data used in this research is quantitative data. The measuring instrument used for this analysis is the SPSS version 25.0. program. This research uses the classic assumption test and is equipped with a multiple linear regression analysis test. The results of this research are based on (t test), tax planning has a partial effect on company value with a sig value of 0,006 < 0,05, while the deffered tax expense has no partial effect on com pany value with a sig value of 0,809 > 0,05. Simultaneously (F test), tax planning and deffered tax expenses have an effect on company value with a value of F count > F table, namely 4,403 > 3.28.